Mechanical properties and microbial assessment of additively manufactured diamond and gyroid Ti-6Al-4V ELI scaffolds for interbody fusion cages applications - Mohit Kumar; Vijay Kumar Meena; Suman Singh (Materials Research Express)
This study investigates the mechanical behaviour and microbial assessment of additively manufactured porous titanium scaffolds for interbody fusion cages applications. This study is meticulously designed to focus on both the mechanical and microbial assessments. Two types of cubic porous structure scaffolds were manufactured. The type 1 scaffold was designed with a diamond structure, featuring a pore size of 500 microns and 65% porosity. Similarly, the type 2 scaffold was designed with a gyroid structure, having a pore size of 500 microns and 65% porosity. Both the types of scaffolds were manufactured using direct selective laser sintering technique. Both the group of scaffolds tested for quasi static compression testing, fatigue compression testing, compression torsional testing and corrosion testing for mechanical properties evaluation. For microbial evaluation, bio burden tests, total organic carbon and total hydrocarbon tests were conducted on the both type of scaffolds. Static compression testing results reported that there is no significant effect on the compression strength properties. Diamond scaffolds had higher yield force value than gyroid scaffolds. Fatigue compression and compression - torsional results reported the higher endurance strength of diamond scaffolds over the gyroid scaffolds. There was no significant difference reported for corrosion behavior of both scaffolds. In the present study, both types of scaffolds demonstrated an almost negligible biological burden. The total organic carbon and hydrocarbons values reported were also under permissible limit as per ISO 19227.Results demonstrated several advantages such as higher endurance strength of diamond scaffolds over gyroid scaffolds, highly corrosion resistance and negligible bio burden limits.